Syllidae Grube, 1850 (Annelida) from Conception, Amanay and Banquete Banks off Canary Islands, with the description of two new species - Núñez, Jorge; Martín, Guillermo San (Zootaxa, 2024)
A study is carried out on the family Syllidae from soft substrates on the marine banks near the Canary Islands. The studied areas were the seamounts Amanay and Banquete Banks (southern off Fuerteventura), and the Conception Bank (north off Lanzarote). Of the 33 species recorded, two are described as new to Science, Exogone martinsosai n. sp. and Syllis guillei n. sp.; ten are cited for the first time for the Canary Islands, Acritagasyllis longichaetous Lucas, San Martín & Sikorski, 2010, Streptodonta exsulis Ramos, San Martín & Sikorski, 2010, Exogone dispar (Webster, 1879), Exogone lopezi San Martín, Ceberio & Aguirrezabalaga, 1996, Parapionosyllis cabezali Parapar, San Martín & Moreira, 2000, Parexogone wolfi San Martín, 1991, Sphaerosyllis boeroi Musco, Çinar & Giangrande, 2005, Plakosyllis brevipes Hartmann-Schröder, 1956, Syllis caeca (Katzman, 1973) and Syllis mercedesae Lucas, San Martín & Parapar, 2012; and two have confirmed their presence in Canary Islands waters, Prosphaerosyllis tetralix (Eliason, 1920) and Sphaerosyllis bulbosa Southern, 1914. The species E. martinsosai n. sp. and S. guillei, n. sp. are described, figured and discussed in detail. Exogone martinsosai n. sp. belongs to a group of this genus sharing some characters: shafts of spiniger-like compound chaetae distally enlarged, spinose and blades relatively short, triangular, which are absent on most anterior segments, and absence of dorsal cirri on the second chaetiger. Syllis guillei n. sp. is defined by its long and slender body, long, thin, whip-shapped dorsal cirri, long pharynx, short proventricle, and compound chaetae with short, bidentate blades with thin, moderately long spines on margin.